The University of Wisconsin-Stout Asynchronous Learning Network Case Study Options: Using Technology to Remove Learning Barriers - Holland, Joseph (Online Learning, 2000)
The University of Wisconsin-Stout Asynchronous Learning Network (ALN) project, funded by the Alfred P. Sloan Foundation, represents an effort to expand the boundaries of the traditional campus. The purpose of this project was to offer learning opportunities to both traditional students and industry professionals either on campus or away from the campus. The asynchronous method of delivery will allow learners to participate from any place at any time. This paper will review how the University of Wisconsin-Stout is using technology to remove learning barriers and provide students with learning options. The focus of this paper is to provide a detailed explanation of the process the University of Wisconsin-Stout used to implement an Asynchronous Learning Network. It will describe the history and background of the project, design and development issues, results and proposed next steps for this campus.